2006
DOI: 10.1007/s10734-004-1391-2
|View full text |Cite
|
Sign up to set email alerts
|

Reshaping Teaching and Learning: The Transformation of Faculty Pedagogical Content Knowledge

Abstract: A qualitative study of faculty members participating in a campus-wide problem-based learning initiative examined the process of transforming faculty pedagogical content knowledge. Researchers found that faculty existing knowledge and the institutional intervention influenced new knowledge of faculty roles, student roles, disciplinary structures, and pedagogy. Communicating new knowledge solidified the transformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
44
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 23 publications
(28 reference statements)
0
44
0
3
Order By: Relevance
“…From global warming to comparative perspectives on immigration to understanding how children learn math around the world, faculty members discovered and integrated a variety of international topics in the courses they taught-one of the key components of curriculum transformation (Allan & Estler, 2005;Hedges, 1996;Schuerholz-Lehr et al, 2007). Importantly, though, participants went beyond just adding additional "special topics" to their courses through individual modules or course sessions and actually saw ways to infuse and integrate international content throughout their courses (Allan & Estler, 2005;Hedges, 1996;Major & Palmer, 2006;Schuerholz-Lehr et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From global warming to comparative perspectives on immigration to understanding how children learn math around the world, faculty members discovered and integrated a variety of international topics in the courses they taught-one of the key components of curriculum transformation (Allan & Estler, 2005;Hedges, 1996;Schuerholz-Lehr et al, 2007). Importantly, though, participants went beyond just adding additional "special topics" to their courses through individual modules or course sessions and actually saw ways to infuse and integrate international content throughout their courses (Allan & Estler, 2005;Hedges, 1996;Major & Palmer, 2006;Schuerholz-Lehr et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Research on professional development programs to encourage curriculum transformation in the fields of multicultural education and Women's Studies has shown that these programs can result in integrating new content into courses, such as new readings, discussion topics, assignments, and class activities (Allan & Estler, 2005;Hedges, 1996). This same research has also identified a number of personal outcomes for faculty participants including changing their pedagogical approaches, coming to accept students as active agents in their own learning, gaining confidence in their teaching abilities, becoming more comfortable discussing potentially controversial issues in the classroom, and coming to understand diversity or other focus issues as fundamental to the core content of their courses rather than treating them as special topics (Allan & Estler, 2005;Hedges, 1996;Major & Palmer, 2006).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…As Major and Palmer (2006) found, institutional support plays an important role in transforming faculty and improving teaching and learning (p. 642). However, like Martensson, Roxå, and Olsson (2011), we see SoTL as a means of not only developing in di vidual staff and faculty members, but more importantly improving the ability of institutions to support student learning (p. 52).…”
mentioning
confidence: 99%
“…Colleges could impact the quality of teaching by providing access to professional development for teachers and providing instruction on teaching methods and techniques (Calcagno & Long, 2008;Elbe, 1988;Kember & Gow, 1994;Major & Palmer 2006;Mishra & Koehler, 2006;Shulman, 1987;Sorcinelli, 2000;Staib, 2003). Furthermore, a systematic approach to the professional development of adjuncts has been shown to enhance instruction and the morale of part-time faculty (Banachowski, 1997;DarlingHammond & Richardson, 2009;Leslie & Gappa, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The creation of campus teaching and learning centers, grants from public and private sources specifically focused on teaching initiatives, publications dedicated to teaching-related research, and national conferences and workshops dedicated to improving teaching are all examples of the burgeoning interests in the development of teaching competence in faculty beyond mere subject matter expertise (Major & Palmer, 2006). This chapter provides a review of the literature as it relates to the role of professional faculty development in supporting teaching and learning at the college level with particular emphasis on part-time faculty.…”
Section: Literature Reviewmentioning
confidence: 99%